2001
DOI: 10.1001/archpsyc.58.11.1057
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Response to Fearful Faces in Anxious and Depressed Children

Abstract: Our results suggest that amygdala function is affected in both anxiety and depression during childhood and adolescence. Moreover, this disruption appears to be specific to the child's own rating of everyday anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

32
337
5
11

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 533 publications
(385 citation statements)
references
References 50 publications
32
337
5
11
Order By: Relevance
“…Studies comparing neural responses to emotionally expressive faces found that the hemodynamic responses of the amygdala were increased when viewing sad faces vs neutral faces or vs fixation point baseline (Fu et al, 2004;Surguladze et al, 2005) in depressives relative to controls. In contrast, hemodynamic responses of the amygdala decreased to fearful faces vs neutral faces in depressed adults relative to controls and to fearful faces vs fixation point baseline in depressed children relative to controls (Thomas et al, 2001). However, left amygdala responses were reportedly increased in depressives vs controls when hemodynamic activity measured during exposure to fearful and happy faces presented using a backward masking technique (so that subjects were unaware of having seen the emotional faces) was compared with activity during fixation point baseline (Sheline et al, 2001).…”
Section: Introductionmentioning
confidence: 85%
“…Studies comparing neural responses to emotionally expressive faces found that the hemodynamic responses of the amygdala were increased when viewing sad faces vs neutral faces or vs fixation point baseline (Fu et al, 2004;Surguladze et al, 2005) in depressives relative to controls. In contrast, hemodynamic responses of the amygdala decreased to fearful faces vs neutral faces in depressed adults relative to controls and to fearful faces vs fixation point baseline in depressed children relative to controls (Thomas et al, 2001). However, left amygdala responses were reportedly increased in depressives vs controls when hemodynamic activity measured during exposure to fearful and happy faces presented using a backward masking technique (so that subjects were unaware of having seen the emotional faces) was compared with activity during fixation point baseline (Sheline et al, 2001).…”
Section: Introductionmentioning
confidence: 85%
“…Given the atypical emotional responses of individuals with anxious or depressive disorders, researchers have hypothesized that anomalies in neural structures involved in perceiving, evaluating, and responding to emotional stimuli may characterize these patient groups. Consistent with this hypothesis, accumulating evidence associates aberrant amygdala function, typically enhanced activity, with anxiety disorders and major depressive disorder (MDD) (2)(3)(4)(5)(6).…”
mentioning
confidence: 97%
“…A smaller body of research in adolescents with mood and anxiety disorders has generated similar evidence of atypical amygdala responsiveness (6,(11)(12)(13), mostly hyperactivity. One study, however, found hypoactivity in a small sample of depressed females (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations